Axial Length, Anterior Chamber Depth, and Lens Thickness in Normal Libyan Eyes; Measured by the Aladdin Ocular Biometer - Bukhatwa, Samar A.; Suliman, Masuod (Libyan International Medical University Journal, 2022)
Background Ocular parameters as axial length (AL), anterior chamber depth (ACD), and lens thickness (LT) are important for refractive and cataract surgeries, and its normal data are important to be identified.Aim This study was carried out to obtain data about AL, ACD, and LT parameters in normal Libyans.Methods A cross-sectional study (first of July to end of August, 2021) was done in Benghazi teaching eye hospital on 106 nondiabetic volunteers aged between 17 and 75 years with no ophthalmic disease. Ocular parameters were measured using the Aladdin optical biometer that is a noninvasive machine and without the use of drugs. Descriptive statistics and data analysis were done by using SPSS version 23.0, IBM Corporation.Results The mean age was 35.36 ±  13.35 years, the mean AL was 23.79 ± 0.91 mm, the mean ACD was 2.96 ± 0.62 mm, and the mean LT was 3.67 ± 0.62 mm. There was no statistically significant difference between these parameters regarding gender or age.Conclusion This is the first study done on Libyan population to report the AL, ACD, and LT. It showed a comparable result with studies from other populations and that age and gender have no effect on these ocular parameters.
Keywords: axial length; anterior chamber depth; lens thickness; normal Libyans